'Through the drawings...they are able to tell you straight': Using arts-based methods in violence research in South Africa. - Nataly Woollett; Nicola Christofides; Hannabeth Franchino-Olsen; Mpho Silima; Ansie Fouche; Franziska Meinck (Public Library of Science (PLoS), 2023)
Arts-based methods are underutilized in violence research and may offer improved means of understanding these phenomena; but little is known about their value, especially in low-resource settings. A pilot study using a cross sectional sample was conducted in rural South Africa to determine the feasibility and acceptability of using arts-based methods in research with adults and children, in preparation for a longitudinal multigenerational cohort study on mechanisms that underly the intergenerational transmission of violence. Four arts-based methods were piloted with young adults aged 22-30 years (n = 29), children aged 4-7 years (n = 21) and former caregivers of the young adults aged 40-69 years (n = 11). A sample of qualitative interviews were audio recorded and transcribed (child n = 15, adults n = 19). Three focus group discussions (FGDs) were conducted to understand implementation and lessons learnt with the six interviewers on the study team, none of whom had used these methods in research before. Interviews and FGDs were audio recorded, transcribed and reviewed by the investigative team. Using a rapid analytical approach, our pilot study demonstrated that using arts and play-based methods in multigenerational violence research is feasible and acceptable to participants and interviewers. These methods worked well for nearly all participants regardless of age or ability and offered a comfortable and 'fun' way to engage in weighty conversations. They presented benefits in their capability to facilitate disclosure, expanding understanding, particularly around violence that is often a stigmatizing and sensitive experience. Interviewers required increased capacity and sensitivity in using the methods carefully, to maximize their full potential, and ongoing mentorship was indicated. Our study adds to the burgeoning evidence base of the effectiveness of the use of arts-based methods in health research.